Religiosity and ritual in the novel Rangsang Tuban by Padmasusastra: Literary anthropology study - Dini, Anggra; Nurhayati, Endang; Endraswara, Suwardi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
Rangsang Tuban by Padmasusastra offers a rich portrayal of Javanese social life through its depiction of traditions, religious practices, and ritual activities that shape the narrative and its characters. This study aims to examine the representation of Javanese religiosity and ritual in the novel and to explore its relevance to contemporary society. The novelty of this research lies in its analysis of ritual practices as expressions of Javanese religious syncretism, revealing interactions between formal religions and local spiritual traditions. Employing a qualitative descriptive method within a literary anthropology framework, this study analyzes textual data in the form of selected quotations obtained through close reading and note-taking. The data are examined through identification, classification, interpretation, and contextual analysis. The findings indicate that the novel reflects a dynamic interaction between Islam, Buddhism, and Javanese spiritual beliefs, manifested in practices such as worship, prayer, scriptural reading, chanting, and puja semedi. These rituals function not only as religious expressions but also as means of constructing spiritual identity and maintaining harmony between humans, nature, and the divine. This study demonstrates that Rangsang Tuban serves as a cultural text that preserves and articulates the continuity of Javanese religiosity in a changing social context.